Low-voltage ride-through strategy for an integrated permanent magnet synchronous generator in a flexible interconnected distribution network - Yang, Lin; Li, Yang; Zhang, Yu; Xie, Zhongren; Chen, Julong; Qu, Yinlong; Shi, Gang (Frontiers in Energy Research, 2024)
For the permanent magnet synchronous generator (PMSG) integrated to the flexible interconnected distribution network (FIDN), its low voltage ride through (LVRT) strategy needs to be designed to enhance the transient operation capability of the FIDN. The design of the LVRT strategy also needs to take the fault location of the FIDN into consideration. To deal with faults occurring on the integrated feeder of the PMSG, the PMSG needs to realize successful LVRT with the help by the hardware protection equipment. To deal with faults occurring on the feeder adjacent to the integrated feeder of the PMSG, the PMSG needs to release its stored energy to temporarily increase its active power output, which is then supplied to the loads on the faulted feeder that are isolated from the fault, through the soft open point (SOP). In this paper, a novel LVRT strategy designed for the PMSG integrated to the FIDN is proposed which includes dual operation modes that are separately applied with different fault locations. If PMSG is on the faulted feeder, the DC-link voltage of the PMSG is maintained with the controllable resistive fault current limiter (CRFCL), while the maximized stored kinetic energy is reserved to enhance the generation efficiency during the LVRT. If PMSG is on the feeder adjacent to the faulted feeder, the control strategy of the converters of the PMSG is adjusted in response to the power regulation goal at the SOP. In the meantime, the maximum releasable kinetic energy of the PMSG is considered when increasing its active power output. The feasibility and effectiveness of the LVRT strategy for the PMSG is verified based on the numerical analysis.